Luminal Conversion and Immunoregulation by Probiotics - Ganesh, Bhanu Priya; Versalovic, James (Frontiers in Pharmacology, 2015)
Beneficial microbes are responsible for the synthesis of nutrients and metabolites that are likely important for the maintenance of mammalian health. Many nutrients and metabolites derived from the gut microbiota by luminal conversion have been implicated in the development, homeostasis and function of innate and adaptive immunity. These factors clearly suggest that intestinal microbiota may influence host immunity via microbial metabolite-dependent mechanisms. We describe how intestinal microbes including probiotics generate microbial metabolites that modulate mucosal and systemic immunity.